Wild women and the blues - Bryce, Denny S. (Kensington Publishing Corp., 2021)
In an award-winning debut novel, a sharecropper's daughter navigates celebrity encounters, bootlegging and gangster activities in Jazz Age Chicago before sharing her story with a grieving film student nearly a century later.